Oral Health of Children with Autism: The Influence of Parental Attitudes and Willingness in Providing Care - Jehan AlHumaid; Balgis Gaffar; Yousef AlYousef; Faris Alshuraim; Muhanad Alhareky; Maha El Tantawi (The Scientific World Journal)
Objectives. Parents play a crucial role in health-related practices of children with autism spectrum disorder (ASD). This study assessed the association between oral health status and oral health practices of children with ASD in relation to their parental attitudes and comfort in providing oral care. Methods. This cross-sectional study included 75 children with ASD attending the special needs schools in Eastern Saudi Arabia from 2015–2018. Parents responded to a self-administered questionnaire assessing their attitudes toward oral health and comfort in providing oral care for children. The clinical examination assessed dental caries (decayed, extracted, and filled: (DMF and def)), gingival disease, and plaque accumulation. The Pearson correlation coefficient was used to assess the relationship between the study variables, while ANOVA followed by post hoc was used to assess the differences. Results. Prevalence of dental caries in primary teeth was 76% and 68% in the permanent dentition with a mean of 0.85 ± 1.9 and 1.03 ± 2.9, respectively. Thirty-one participants had gingival problems, mean gingival index was 1.03 ± 0.88, and mean plaque index was 0.95 ± 0.43. Half of the parents supervised their children’s brushing, which was significantly associated with plaque accumulation (p = 0.004), gingival disease (p < 0.0001), and def (p = 0.02). Parental attitudes and comfort in providing oral health care were not associated with oral health status of ASD children; however, positive parental attitudes were associated with lower sugar consumption (p = 0.043). An inverse correlation was observed between comfort in providing oral health care with gingival and plaque scores r = −0.18 and −0.23, respectively. Conclusions. The data are indicative of poor oral health practices and status among ASD children. Parents’ oral health care practices seem to be reactive rather than proactive. Positive parental attitudes were associated with lower sugar consumption. Greater comfort in providing care was negatively correlated with plaque accumulation and gingival problems.